Imaging with Optogenetically Engineered Living Cells as a Photodetector. Issue 8 (21st June 2019) - Li, Gongxin; Wang, Feifei; Yang, Wenguang; Wang, Wenxue; Li, Guangyong; Wang, Yuechao; Liu, Lianqing
Abstract: Biosyncretic systems integrating biological components with electromechanical devices have recently become a promising technology, in which biological components are used as actuators or sensing elements with higher‐level performance than artificial systems. Here, a biosyncretic imaging system using an optogenetically engineered living cell as a photodetector is shown. The photoresponsive properties of the cell, such as spectrum and response range, dynamic characteristics, are measured and indicate that the cell functions as an excellent photodetector. In the system, the cell is directly utilized to generate light‐triggered ionic currents, which encode the spatial image information and therefore are used to reconstruct the scenes under the view based on compressive sensing. Imaging with the cell‐based photodetector is successfully performed by acquiring high‐definition images using the system. The system also displays function superiority to a commercial photodiode, such as wider dynamic responsivity range. This work represents a step toward directly imaging with living materials and paves a new road for the development of future on‐body bionic devices. Abstract : A biosyncretic imaging system integrating biological components with electromechanical devices is established with an optogenetically engineered cell, which successfully acquires high‐resolution images based on the compressive sensing theory. This work represents a step toward directly imaging with living materials and paves a new road for the development of future on‐body bionic devices.